Measurement of the cross section for diffractive deep-inelastic scattering with a leading proton at HERA - Aaron, Francisc Dionisie; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2011)
The cross section for the diffractive deep-inelastic scattering process ep→eXp is measured, with the leading final state proton detected in the H1 Forward Proton Spectrometer. The data sample covers the range xℙ<0.1 in fractional proton longitudinal momentum loss, 0.1<|t|<0.7 GeV2 in squared four-momentum transfer at the proton vertex and 4<Q2<700 GeV2 in photon virtuality. The cross section is measured four-fold differentially in t,xℙ,Q2 and β=x/xℙ, where x is the Bjorken scaling variable. The t and xℙ dependences are interpreted in terms of an effective pomeron trajectory and a sub-leading exchange. The data are compared with perturbative QCD predictions at next-to-leading order based on diffractive parton distribution functions previously extracted from complementary measurements of inclusive diffractive deep-inelastic scattering. The ratio of the diffractive to the inclusive ep cross section is studied as a function of Q2,β and xℙ.